Making The Workplace 'Safe' in Capitalism: The Enforcement of Factory Legislation in Nineteenth-Century Ontario - Tucker, Eric (Labour/Le Travailleur)

(untitled) (Canadian Committee on Labour History, 1988)
Abstract The development of industrial capitalism in the second half of the nineteenth century in Ontario brought new and more serious hazards into the workplace and drew women and children into the waged labour force. As a result of working class lobbying and the efforts of middle class reformers, the state empowered itself to regulate health and safety conditions in factories and to protect child and female labour. The implementation of these regulations was left to an inspectorate which was armed with substantial legal powers to enforce the law. These powers were rarely invoked by the inspectors. However, the failure to prosecute does not in itself indicate that the law was unenforced. An alternative enforcement strategy based on persuasion was followed by most inspectors. It has been argued that persuasion was chosen over prosecution because it made more efficient use of the scarce enforcement resources available to the inspectors, and that persuasion was effective. This paper argues that although it is true that the government chose to devote woefully inadequate resources to enforcement of factory legislation, this is not an adequate explanation of the inspectors' enforcement behaviour. The belief that persuasion was an effective enforcement model also flowed from the inspectors' values and assumptions, including the following: that worker carelessness was the major cause of accidents; that employers were socially responsible; that workers and employers had common interests in occupational health and safety; and that women and children needed special protection. It is further argued that persuasion was not an effective enforcement strategy, especially because it was linked with an acceptance by the inspectors of 'normal' industrial practices, even where those practices generated significant risks for workers. In effect, health and safety regulation probably did as much to legitimate industrial capitalism as it did to protect workers health and safety.